A systematic review on the seroprevalence and global distribution pattern of paratuberculosis in small ruminant and deer herds - Jimale, Yonis Ahmed; Paul, Bura Thlama; Jesse, Faez Firdaus Abdullah; Rosmidi, Mohamad Afiq Ikhwan; Chung, Eric Lim Teik; Mohd Lila, Mohd Azmi (Assiut University, 2024)
Paratuberculosis, also known as Johne's disease, is a chronic wasting disease caused by Mycobacterium avium subs paratuberculosis (MAP) in ruminants. Paratuberculosis causes a significant reduction of milk production in the affected dairy sheep or goats and increase the cost of diagnosis, treatment, and culling of the infected animals. Paratuberculosis is currently recognised as a disease of major economic significance in cattle, sheep, goats, and wild ruminants globally. Recent reports also suggest that paratuberculosis affects wild ruminants and farmed deer. Despite the widespread occurrence of MAP, there are variations in the seroprevalence and global distribution patterns of disease among small ruminants and deer herds due to the influence of interacting epidemiological variables in different places. This systematic review aims to provide insights on the current global seroprevalence status and distribution pattern of paratuberculosis among small ruminants and deer herds. The review compiled, analyzed, and narratively synthesized 36 eligible research articles published between January 1, 2010, and January 31, 2024, from the SCOPUS and PubMed databases based on the 22-point Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist. The average global seroprevalence of paratuberculosis in sheep was 14.02% (0.7–66.8), with the highest rate in Canada (66.8%) and the lowest in Austria (0.7%). Comparatively, the average global seroprevalence in goats was 18.44% (0.3–83), with the highest rate in Canada (83%) and the lowest in the West Indies (0.3%). The average global prevalence of paratuberculosis in deer was 14.76% (3.7–30.2), with the highest rate in Spain (30.2%) and the lowest rate in the Czech Republic (3.7%). This review revealed that Canada is a hot spot for both caprine and ovine paratuberculosis, and there were higher global seroprevalence rates in goats than sheep and deer. The lack of data on the seroepidemiology of paratuberculosis among small ruminant stock in Southeast Asia and other regions is a gap in our current knowledge of its distribution. Therefore, seroprevalence surveys of paratuberculosis among small ruminant and deer livestock are required to furnish information for planning suitable interventions in these areas.